Green Nanotechnology The Latest Innovations, Knowledge Gaps, and Future Perspectives - Martins, Roberto; Kaczerewska, Olga Barbara (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This Book presents original research articles published in the Special Issue entitled "Green Nanotechnology: The Latest Innovations, Knowledge Gaps, and Future Perspectives". It proposes pioneering and innovative applications, products, technologies, and processes in several green nanotechnology-related fields (e.g., drug delivery systems, antifouling nanoadditives, and coatings for optical applications), as well as identifying some knowledge gaps on this domain. Research on the sustainable production of nanomaterials based on safe-by-design approaches and (eco)toxicological assessments of novel nanomaterials is also provided. Future perspectives are also highlighted in the Editorial and across the original articles.